An Analysis of Assertive and Commissive Speech Acts in Simon Sinek’s Speeches - Kholid, Idham; Hidayat, Agus; Triyani, Bela (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
This research discusses speech act analysis, focusing on assertive and commissive illocutionary speech acts in Simon Sinek’s speech. The subject of this research is a video of Simon Sinek’s speech. This research aims to identify the types and functions of assertive and commissive speech acts used in Simon Sinek's speeches based on Searle and Vanderveken's theory. The design of this research is qualitative descriptive, using documentation to obtain data. In analyzing the data, the researcher followed steps by Miles and Huberman, which include data collection, data presentation, and drawing conclusions. The results of the analysis of Simon Sinek's speech video revealed a total of 56 utterances categorized as assertive and commissive speech acts. Among the assertive acts, there were 1 instance of asserting, 3 of claiming, 6 of affirming, 5 of stating, 5 of reporting, 4 of informing, 5 of notifying, 4 of reminding, 3 of predicting, and 8 of suggesting. Notably, there were no utterances classified as admitting. Among the commissive acts, there were 3 instances of consenting, 4 of refusing, 4 of offering, and 1 of threatening. Based on the findings, assertive illocutionary speech acts were more dominant than commissive speech acts